Characterization and mitigation of emerging bunyaviruses - Ayers, Victoria Brittany (Kansas State University, 2022)
Bunyavirus is a general term used to describe segmented, negative-sense, single-stranded RNA viruses that are considered important emerging pathogens which can play a significant role in veterinary and human public health. As a diverse group of mostly arthropod-borne viruses, they have recently been moved into the Bunyavirales order, which is the largest group of RNA viruses. Within the Bunyavirales order, Cache Valley virus (CVV) and Rift Valley fever virus (RVFV) play a significant role in veterinary and human morbidity and mortality. Presently, there are no vaccines available to prevent or control CVV and although there are RVFV veterinary vaccines, they have limitations. To address the limitations and gaps in knowledge for CVV and RVFV, several approaches were taken to advance our understanding of bunyavirus transmission and evaluate potential mitigation strategies. The objective of this dissertation was to identify competent mosquito vectors involved in the transmission of CVV and to evaluate candidate live-attenuated vaccines for CVV and RVFV to improve prevention, control, and mitigation strategies for emerging bunyaviruses. The hypothesis for this dissertation is that recombinant live-attenuated candidate vaccines for CVV and RVFV are sufficiently immunogenic and attenuated in animals and unable to replicate in medically important mosquitoes in North America. Aim 1 determined the vector competence of medically important mosquito species in North America for the transmission of CVV. It was determined that Culex (Cx.) tarsalis, Aedes (Ae.) aegypti, and Ae. albopictus were susceptible to CVV and are competent for transmission of CVV in North America. These results provide a basis for how the dispersal of Aedes and Culex species mosquitoes across North America may significantly impact the transmission and ecology of CVV. Aim 2 characterized a candidate live-attenuated vaccine (2delCVV) for CVV lacking the NSs and NSm genes. First, the immunogenicity of the live-attenuated 2delCVV candidate vaccine, lacking the expression of the two nonstructural genes (NSs and NSm) was evaluated and compared to an autogenous binary ethylenimine (BEI) inactivated CVV vaccine (BEI-CVV), in sheep. An autogenous vaccine was used for comparison because this type of vaccine can be approved and used by veterinarians when there are no vaccines commercially available. Although there was no significant difference in the neutralizing antibody titers, the 2delCVV candidate vaccine induced a slightly higher neutralizing antibody response than the autogenous vaccine on day 63 post-initial immunization. More importantly, 2delCVV elicited neutralizing antibody titers that could potentially confer protection against wild-type CVV through the duration of the study. After demonstrating attenuation of the live-attenuated 2delCVV candidate vaccine in sheep, the growth kinetics of 2delCVV in Ae. albopictus mosquitoes was evaluated. Ultimately, mosquitoes injected with the 2delCVV candidate vaccine had significantly lower infectivity than the mosquitoes injected with wild-type CVV, demonstrating restricted replication. These data provide a basis for further developing immunogenic vaccines for CVV and other bunyaviruses. Aim 3 demonstrated the immunogenicity of a candidate live-attenuated RVFV vaccine in CD-1 mice. Using a similar approach as described for CVV, a reverse genetics system was utilized to create a live-attenuated candidate vaccine lacking the NSs and NSm genes (r2segMP12) and modified the three-segmented genome into a two-segmented genome. The regimen of a single immunization administered at an increasing dosage per group was included to determine the correlation of neutralizing antibodies induced by different dosages. The immune response induced by the live-attenuated vaccine candidate was then compared to the neutralizing antibody titer produced by the conditionally licensed rMP12 parental vaccine strain. The r2segMP12 candidate vaccine at 10⁵ PFU elicited a significantly higher neutralizing antibody response than the rMP12 vaccine at the same vaccination titer. The candidate vaccine, r2segMP12, was given as a booster dose at 10⁵ PFU to assess if it would increase immunogenicity and produce a long-lasting neutralizing antibody response. Mice that received a single immunization of the r2segMP12 candidate vaccine at 10⁵ PFU established a seroprotective neutralizing antibody response with a significantly higher immune response than those that received the rMP12 vaccine at the same titer. These results suggest that the superior immunogenicity of the r2segMP12 strain as compared to the rMP12 strain warrants its advancement in the process of vaccine development for RVFV and other bunyaviruses. This work identified competent mosquito vectors and evaluated candidate live-attenuated vaccines for CVV and RVFV, which will aid in improving prevention, control, and mitigation strategies against emerging bunyaviruses. Results presented in this dissertation confirmed multiple North American mosquito species are competent vectors for the transmission of CVV, with the potential to contribute to the epizootic and enzootic transmission cycle of this virus. Developing a vaccine for CVV and RVFV is an important step to preventing future outbreaks, additionally, the methods to create these candidate vaccines could be a feasible approach to developing attenuated vaccine candidates for other emerging bunyaviruses.
Keywords: Bunyavirus; Cache Valley virus; Rift Valley fever virus; Live-attenuated vaccine